2017
DOI: 10.1111/jon.12436
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopy in Patients with Nonlesional Insular Cortex Epilepsy Confirmed by Invasive EEG Recordings

Abstract: Our preliminary findings suggest that H-MRS fares poorly in identifying patients with nonlesional insular epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The value of proton MRS in identifying patients with insular epilepsy was assessed in 12 nonlesional cases with confirmed operculo-insular focus. 19 Voxels were positioned to include bilateral anterior and posterior insular regions. Metabolite concentrations and ratios did not differ from those of noninsular epileptic patients and healthy controls, and asymmetry indices fared poorly in lateralizing the focus.…”
Section: Noninvasive Investigation Of Operculo-insular Epilepsymentioning
confidence: 99%
“…The value of proton MRS in identifying patients with insular epilepsy was assessed in 12 nonlesional cases with confirmed operculo-insular focus. 19 Voxels were positioned to include bilateral anterior and posterior insular regions. Metabolite concentrations and ratios did not differ from those of noninsular epileptic patients and healthy controls, and asymmetry indices fared poorly in lateralizing the focus.…”
Section: Noninvasive Investigation Of Operculo-insular Epilepsymentioning
confidence: 99%
“…Although operculoinsular epilepsy is relatively rare, it accounts for a non-negligible proportion of drug-resistant epilepsy surgical candidates and sometimes it can be difficult to be recognized (4)(5)(6). Because of the complex physiology and the rich connections to surrounding and remote structures, the clinical manifestations of operculoinsular seizures can be diverse (7).…”
Section: Introductionmentioning
confidence: 99%
“…These findings denied the value of these ratios in identifying the patients with non-lesional epilepsy. This went with Aitouche et al who found that the measurement of absolute NAA and NAA/Cr ratio cannot differentiate between non-lesional insular epilepsy, extra insular epilepsy, and control groups [9].…”
Section: Discussionmentioning
confidence: 56%
“…One study studied MRS in nonlesional insular cortex epilepsy. They used both singlevoxel spectroscopy (SVS) and multi-voxel spectroscopy techniques [9]. However, to our knowledge, no studies were dedicated to study SVS in non-lesional epilepsy in pediatric age group (after advanced research using PMC, pub Med, Google scholar and research gate data base up to November 2019).…”
Section: Introductionmentioning
confidence: 99%